Augmented simvastatin cytotoxicity using optimized lipid nanocapsules: a potential for breast cancer treatment. (2nd January 2017) - Safwat, Sally; Hathout, Rania M.; Ishak, Rania A.; Mortada, Nahed D.
Abstract: Context : We noticed paucity in exploiting solutol-based lipid nanocapsules in statins formulations though they carry all favorable properties that are needed for cancer passive targeting such as their small particle size, stealth properties, ability to highly accommodate lipophilic drugs, good internalization and P-gp pump inhibition. Objective : The aim of this study was to design and optimize new simvastatin drug delivery systems; lipid nanocapsules intended for administration through the intravenous route as potential treatment for breast cancer. Methods : Optimized nanocapsules were prepared by the phase-inversion method according to a D-optimal mixture design, characterized and assessed for their cytotoxicity. Results : Three successful models for particle size, polydispersity index (PDI) and percentage of drug released after 48 h were generated. The prepared lipid nanocapsules acquired spherical and homogenous morphology, good stability and tolerance to sterilization. The obtained release profiles demonstrated desired sustained release pattern. Furthermore, testing selected formulations on human breast cancer adenocarcinoma cells showed augmented cytotoxicity of simvastatin reaching low IC50 values as 1.4 ± 0.02 μg/ml compared to the pure drug. Conclusion : The proposed lipid nanocapsules pose promising candidates as simvastatin carriers intended for the targeting of breast cancer.